(untitled) (Global Journal of Management and Business Research, 2021)
Amid a global health crisis, several countries have announced the start of containment and a state of health emergency, in order to mitigate the spread of the virus. A series of measures have been recommended in order to spare populations from serious health dangers. This is how COVID-19 created an economic, financial and social crisis. This article identifies the effects of the crisis linked to the coronavirus pandemic on earnings management. It sheds light on the practices of income management that have also been affected following this pandemic. The article also lists a series of accounting manipulation techniques adopted by executives in today’s environment.